EFFECT OF DIFFERENT LEVELS OF DEFOLIATION ON INFLORESCENCE SAP YIELD AND TENDER FRUIT ENDOSPERM YIELD IN PALMYRAH (Borassus flabellifer L.) - G.N. MURTHY, K.T.V.RAMANA, M.S. RAJU AND P.C VENGAIAH (The Journal of Research ANGRAU, 2015)
Palmyrah palm adorns the dry landscape of the semi arid tropics of Tamil Nadu, Andhra Pradesh, Odisha,West Bengal, Karnataka and Maharastra. Palmyrah trees thrive in non-agricultural lands, on the banks of streams,rivers, canals, undulating hill slopes and sandy lands which are normally unfit for cultivation. Inflorescence sap(Neera) is the top most economic produce of palmyrah. For the convenience and easy access during inflorescencesap tapping, farmers are defoliating more than ninety percent of the leaves and as a result the inflorescence sapyields are drastically getting reduced. To know the effect of defoliation on inflorescence sap and tender endosperm(Nungu) yields in palmyrah a study was conducted at Horticultural Research Station, Pandirimamidi with four differentlevels of defoliation i.e., 30%, 50%, 70% and 90% defoliation from the years 2010 to 2012. The control plants were leftwithout defoliation. Data was recorded on different parameters like inflorescence sap yield (neera), days for initiationof flowering after defoliation, number of bunches plant-1, number of inflorescences tapped and mean yield of tenderfruit endosperm /bunch (kg). The results revealed that total yield of inflorescence sap was highest in 30% defoliatedpalms (194.8 l) followed by Control (158.8 l) in male palms. In female palms also 30% defoliated palms recorded thehighest inflorescence sap (210.5 l) followed by Control (193.6 l). Lowest inflorescence sap yields was recorded with90% defoliated palms in both male(119.5 l) and female(105.4 l) palms. The yield of tender fruit endosperm (Nungu)per bunch was maximum in control palms (2.16 kg/bunch) which were followed by 30% defoliated palms (1.95 kg).Minimum tender fruit endosperm yield per bunch was recorded with 90% defoliated palms (0.98 kg). The number offruit bunches produced plant-1 was maximum (8.61) in control plants followed by 30% defoliated palms (7.96).Minimum number of bunches were recorded with 90% defoliated palms.